Increased Added Value Of Fish Wasted In Efforts To Commercialize Competitive Products And Based Information Technology - Shalahuddin; Mohamad Nur Utomo; Kaujan; Widyastuti Cahyaningrum; Erick Karunia (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
The community service plan (PKM) in this article aims to inform the community about the use of marine resources in the coastal area of Tarakan to increase economic value, The target to be achieved in this program is for the target group to be able to optimize the results of marine resources, especially the use of wasted fish to boost their economy. This activity is carried out through lectures and discussions with partners or community groups who want to market their products, by providing understanding and training in efforts to commercialize competitive products, and of course through information technology so that they can add value for their income. This kind of discarded fish processing business or business is carried out by partners who want to help their household finances. Wastaged fish processed products that have been produced by partners in the PKM grant are further proposed. There are several problems faced, especially in the commercialization and marketing process. The next problem faced by partners is how to make marketing and commercialization media to be able market their products and can be known by all levels of society. The method used in this event is: First, give guidance through brainstorming to open up the mindset about the importance of marketing media and commercialization in order to be able to market their products. The second is consulting on management and commercialization or marketing processes as a determinant of the success of the waste fish processing business in terms of production and management. The output of this activity includes: 1). Aspects of commercialization, namely increasing product marketing so as to increase added value, as well as the use of information technology media. 2). The management aspect is the management of the sustainable management system, that is, the marketing management that has a wide range of influence and is well-known to the public. As a result, partners can understand the benefits, commercialization and effective marketing. In addition, partners can also understand the importance of using information technology to market their products.